Improved outcomes following addition of bedaquiline and clofazimine to a treatment regimen for multidrug-resistant tuberculosis. Issue 1 (January 2023) - Yao, Ge; Zhu, Muxin; Nie, Qi; Chen, Nanshan; Tu, Shengjin; Zhou, Yong; Xiao, Fan; Liu, Yuan; Li, Xi; Chen, Hua
Objective: To investigate if the addition of bedaquiline and clofazimine to a treatment regimen for multidrug-resistant tuberculosis (MDR-TB) could improve patient outcomes. Methods: A prospective, randomized, controlled study was conducted in patients with MDR-TB. Treatment was for 18 months. Patients in the experimental group received bedaquiline and clofazimine in addition to their regular treatment regimen whereas patients in the control group did not. Results: 68 patients with MDR-TB were randomised to treatment, 34 to each group. At the end of treatment, cure rates were statistically significantly greater for the experimental group compared with the control group (82% vs. 56%). There was no difference between groups in the number of severe adverse events (3[9%]) in both groups and none were skin-related. Conclusions: The addition of bedaquiline and clofazimine to the treatment regimen significantly improves outcomes for patients with MDR-TB. Clinicians should be aware of the clinical benefits of this addition but be mindful of contraindications and adverse effects.